Not to be impolite, but this is war: How the impolite strategy of challenge is utilised and countered in debates between atheists and Christians - Górska, Aleksandra; Drogosz, Anna (Papers in Linguistics, 2019)
W artykule analizowane są wybrane debaty między chrześcijanami i ateistami/ ewolucjonistami z punktu widzenia strategii niegrzeczności i kontrstrategii.